2012
DOI: 10.1155/2013/714063
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Antidiabetic Effects of Different Parts of Cassia fistula Linn, a Southeast Asian Plant

Abstract: The hypoglycemic effect of the methanolic and aqueous extracts of whole parts ofCassia fistulain both normoglycemic and streptozotocin-nictotinamide induced Type 2 diabetic rats were investigated. Acute toxicity, oral glucose tolerance test and glucose uptake in isolated rat hemidiaphragm were performed in normal rats. Diabetes was induced in Sprague Dawley rats by the administration of streptozotocin-nictotinamide (50, 110 mg/kg b.w., resp.) intraperitoneally. Different extracts ofCassiawas administered to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In addition to this, the extract may cause inhibition of glucose absorption in the gut. 35,38,39,54 Daisy et al, (2010) reported that catechin isolated from methanolic extract of C. fistula bark has significant hypoglycemic and insulin mimetic effect in STZ-induced diabetic rats. 35 Previous studies conclusively have shown that phytochemicals like, proanthrocynadins, 55 kaempferol, 56 quercetin 57,58 and anthroqunone derivatives 59,60 possess hypoglycemic effects in the diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, the extract may cause inhibition of glucose absorption in the gut. 35,38,39,54 Daisy et al, (2010) reported that catechin isolated from methanolic extract of C. fistula bark has significant hypoglycemic and insulin mimetic effect in STZ-induced diabetic rats. 35 Previous studies conclusively have shown that phytochemicals like, proanthrocynadins, 55 kaempferol, 56 quercetin 57,58 and anthroqunone derivatives 59,60 possess hypoglycemic effects in the diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent histopathology studies of the pancreas also demonstrated the comparable regeneration of pancreatic β-cells by the aqueous extract, which was earlier necrosed by alloxan, directed that the extract might be of potential value for diabetes management. Einstein, Mohd Rais, and Mohd (2012) reported that the methanol extract of leaves and bark of C. fistula started promoting the antihyperglycemic effect in streptozotocininduced diabetic rats from the seventh day and attaining the maximum beneficial potential on 21st day of administration. In diabetic rats, the elevated blood glucose levels, increased glycosylated hemoglobin levels, and reduced plasma insulin levels were significantly resumed to normal after the oral administration of methanol extract of leaves and bark at the dose of 500 mg/kg.…”
Section: Antiasthmatic Activitymentioning
confidence: 99%
“…[93] Methanolic and aqueous extracts of whole parts of C. fistula exhibit hypoglycemic effect both in normoglycemic and streptozotocin-nicotinamide induced Type 2 diabetic rats. [94] Anticonvulsant Cassia siamea contains barakol a potential anxiolytic agent [95] that causes lowering of intraocular pressure in a DBA/2J mouse glaucoma model. [96] Cassia species are also used for treating epilepsy by indigenous communities of sub-Himalayan region of Uttarakhand [ Table 1].…”
Section: Antidiarrheamentioning
confidence: 99%